PENGARUH KECERDASAN EMOSIONAL, KARAKTERISTIK PEGAWAI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN TIMUR - Yusrani Lubis (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The formulation of the problem in this research is how the influence of  emotional intelligence on employees  performance. How  influence of  employees characteristic on employees  performance. How  influence of   work motivation on employees  performance. How  influence of   emotional intelligence,  employees characteristic and   work motivation on employees  performance. The purpose of this research is for know influence and analize of   emotional intelligence on employees  performance. For know influence and analize of  employees characteristic on employees  performance. For know influence and analize   work motivation on employees  performance. For know influence and analize  emotional intelligence,  employees characteristic and   work motivation on employees  performance.  The sample in this research is 86 employees, with data analysis technique used is multiple linear regression analyze. The results of this research explain that  emotional intelligence effect has a positive and significant on employee  performance.  employees characteristic effect has a positive and significant on employee  performance.   work motivation effect has a positive and significant on employee  performance.  emotional intelligence,  employees characteristic and   work motivation effect  have a positive and significant on employee  performance